Change in Body Weight and Ovary Weight of Pre-lay Pullets Fed Maize-soy Based Diet Supplemented with an Exogenous Microbial Enzyme - Navaporn Chauynarong; Paul Iji; Supaporn Isariyodom; Mingan Choct; Lene Mikkelsen (Agriculture and Natural Resources, 2007)
The experiment was conducted to examine the benefits of supplementing maize-soy diets with a composite microbial enzyme, Allzyme SSF®, for laying hens at the pullet stage. Seven hundred and twenty (720) 12-week old Isa Brown pullets were treated in the different level of protein content diets. The three diets contained 120, 140 and 160 g CP/kg, each fed with or without a microbial enzyme supplement, Allzyme SSF® (200 g/ton), in a 3 x 2 factorial design. The three main diets were designated as Low-CP, Mid-CP and High-CP, respectively. In experiment, feed intake from 12 to 16 weeks of age was unaffected by the enzyme supplement, except at the lowest protein content (P<0.05). Feed intake was, however, affected by the enzyme supplement between 16 and 20 weeks (P<0.001) and over the entire trial period (P<0.05). Body weight at 16 weeks of age was reduced (P<0.05) on the control lowprotein diet. Feed conversion ratio was not affected by dietary protein content or through supplementation with the microbial enzyme. The relative weight of the ovary was reduced (P<0.01) on the low protein control diet. Onset of lay occurred from about 23 weeks of age, after the hens were already on a commercial diet but effects of previous dietary treatments on early egg production were noticeable. The current results suggest that supplemental Allzyme SSF is beneficial to growing pullets on low protein diets, and the supplement supports egg production in early lay.